Effects of acne severity and acne-related quality of life on depressive symptoms among adolescents and young adults: a cross-sectional study in Bangladesh - Tasneem, Takfi; Begum, Afroza; Chowdhury, Mohammad Rocky Khan; Rahman, Syed; Macassa, Gloria; Manzoor, Jasmin; Rashid, Mamunur (Frontiers in Psychology, 2023)
Introduction: Depression is a common mental health disorder and one of the major causes of disability. This study aimed at investigating the relationship of acne severity and acne-related quality of life with depressive symptoms, and the mediating effect of acne-related quality of life in a relationship between acne severity and depressive symptoms. Methods: This is a cross-sectional study. Data were collected from acne patients attending a tertiary-level hospital, using a questionnaire that comprised three validated instruments – Investigator’s Global Assessment (a single item) scale, Cardiff Acne Disability Index, and Beck Depression Inventory for measuring acne severity, acne-related quality of life, and depressive symptoms, respectively. Logistic regression and linear regression were used to examine the association between acne severity and depressive symptoms and a correlation between the acne-related quality of life and depressive symptoms, respectively. A mediation analysis was also performed to see the mediation effects of acne-related quality of life in a relationship between acne severity and depressive symptoms. Results: A total of 185 acne patients (155 females, 83.8%) with a mean age was 22.55 ±8.67 years were included in the study. Adolescents and young adults with severe and moderate acne had 6.14- and 2.28 times higher odds of depression compared to their peers with mild acne, respectively. Patients with low levels of acne-related quality of life had a higher level of depressive symptoms (β= 0.42, p < 0.001). The total effect (direct + indirect) was also significant (β= 0.27, 95% CI: 1.29–4.09), implying the effect of acne severity on depression. Conclusion: The present study suggests that acne severity and acne-related quality of life were associated with depressive symptoms among patients with acne vulgaris. The study also indicates that the relationship between acne severity and depressive symptoms might occur through a chain-mediating effect of acne disability in this population.